Climatic warming strengthens a positive feedback between alpine shrubs and fire. (27th January 2017) - Camac, James S.; Williams, Richard J.; Wahren, Carl‐Henrik; Hoffmann, Ary A.; Vesk, Peter A.
Abstract: Climate change is expected to increase fire activity and woody plant encroachment in arctic and alpine landscapes. However, the extent to which these increases interact to affect the structure, function and composition of alpine ecosystems is largely unknown. Here we use field surveys and experimental manipulations to examine how warming and fire affect recruitment, seedling growth and seedling survival in four dominant Australian alpine shrubs. We found that fire increased establishment of shrub seedlings by as much as 33‐fold. Experimental warming also doubled growth rates of tall shrub seedlings and could potentially increase their survival. By contrast, warming had no effect on shrub recruitment, postfire tussock regeneration, or how tussock grass affected shrub seedling growth and survival. These findings indicate that warming, coupled with more frequent or severe fires, will likely result in an increase in the cover and abundance of evergreen shrubs. Given that shrubs are one of the most flammable components in alpine and tundra environments, warming is likely to strengthen an existing feedback between woody species abundance and fire in these ecosystems. Abstract : We used field surveys and experimental manipulations to examine how warming and fire affect shrub seedling recruitment and growth and survival. We found that warming, coupled with more frequent or severe fires, will likely increase the cover and abundance of evergreen shrubs—a major fuel for alpine fires. As a consequence, warming is likely to strengthen an existing feedback between shrub abundance and fire in these ecosystems.